A record of hypertrophy of the tragus of great fruit-eating bat Artibeus lituratus (Chiroptera: Phyllostomidae) - Tamayo-Zuluaga, Andrés F. (2020)
In this work, we report and describe evidence of an anomaly in the tragus of an individual of Artibeus lituratus, captured in the Central Andes of Colombia. During field work in the Department of Caldas, municipality of Aranzazu, one individual of A. lituratus with unusual tragus form was trapped. This individual had a tragus with cylindrical shape and asymmetry. The individual was collected and deposited at the Museum of Natural History of the University of Caldas (MHN-UCa). A literature review was conducted to find similar cases using searching engines, but no previous reports of the anomaly were find. Furthermore, we reviewed the tragus of vouchers at the MHN-UCa and none of these had similar malformations. We concluded that this anomaly has not previously registered in Chiroptera.